(untitled) (Jurnal Bina Praja, 2018)
Indonesia has been practicing both symmetric and asymmetric decentralization for decades. This study believes that asymmetric decentralization should not only for those five provinces (Jakarta, Yogyakarta, Aceh, Papua and West Papua). If political considerations and the effectiveness and efficiency of government, asymmetric decentralization becomes a necessary choice for many other regions in Indonesia. This includes autonomous regions characterized by islands (archipelagic regions). Hence, this paper will discuss a number of reasons why archipelagic regions also need asymmetrical arrangements. How to make such arrangements functional? What potential challenges might be encountered? This study employs qualitative approach with theory-driven type. Operationally, this study is sustained by a series of Focus Group Discussion (FGD) and documentary method. Aiming at strengthening the capacity of the government for more effective governance and development process, the uniqueness and various specific problems faced by archipelagic regions become the main reasons for applying asymmetric decentralization. Proposing a separate policy provides an effective strategy for certainty and functional de jure and de facto asymmetry arrangements. Handling various existing problems which could weaken the capacity to carry out asymmetric decentralization policy would be the most appropriate strategy to make the policy facilitates its potential benefits.